Clinical evaluation of the bicoronal flap in the treatment of facial fractures. Retrospective study of 132 patients - Gabrielli, Marisa Aparecida Cabrini [UNESP]; Monnazzi, Marcelo Silva [UNESP]; Real Gabrielli, Mario Francisco [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Mendes Dantas, Marcos Vinicius [UNESP] (Elsevier, 2012)
The aim of the present study was to evaluate the postoperative complications of bicoronal flaps used to treat facial fractures. One hundred and thirty two patients that received bicoronal flaps for the treatment of upper and middle third facial fractures were called for clinical and radiographic examination. Minimum follow-up was 1 year and all patients had charts with adequate information about their perioperative care pertinent to the study. Results showed as complications hypoesthesia (17%), partial unilateral frontal motor deficit (11%), infection (3%), hypertrophic scars (3%), varying degrees of alopecia (18%), seroma or hematoma in the immediate postoperative period (5%). The flap provided wide surgical access to the upper and middle facial thirds with very few serious complications, most frequently allowing good aesthetic results. © 2011 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: Bicoronal flap; Facial fractures; Middle facial third